2017
DOI: 10.1085/jgp.201611737
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of light-activated channels TRP and TRPL in photoreceptors of Periplaneta americana

Abstract: Insect photoreceptors utilize two light-activated channels, TRP and TRPL, in their phototransduction cascades, but the American cockroach Periplaneta americana depends strongly on TRPL. Saari et al. show that TRPL generates high-gain and high-noise phototransduction suitable for dim light vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 31 publications
(80 reference statements)
6
19
0
Order By: Relevance
“…Although decreased quantum efficiency is consistent with our findings of the relatively low absolute sensitivities in both knockdowns, and also with the previous findings in D. melanogaster (Hardie et al 2002), this effect cannot be separated from the loss of absolute sensitivity associated with what we consider the non-specific changes in the photoreceptor, especially with the reduced C m [the relations between absolute sensitivity and C m are discussed at length in Frolov et al (2018)]. These presumably compensatory changes are similar to those documented previously in other cockroach retinal protein knockdown experiments Saari et al 2017). Interestingly, increased ionic permeability of photoreceptor membrane at rest was also described in ion channel mutants in D. melanogaster (Vähäsöyrinki et al 2006), suggesting the presence of intrinsic mechanisms that upregulate leak conductance(s) to substitute for a missing ion channel.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Although decreased quantum efficiency is consistent with our findings of the relatively low absolute sensitivities in both knockdowns, and also with the previous findings in D. melanogaster (Hardie et al 2002), this effect cannot be separated from the loss of absolute sensitivity associated with what we consider the non-specific changes in the photoreceptor, especially with the reduced C m [the relations between absolute sensitivity and C m are discussed at length in Frolov et al (2018)]. These presumably compensatory changes are similar to those documented previously in other cockroach retinal protein knockdown experiments Saari et al 2017). Interestingly, increased ionic permeability of photoreceptor membrane at rest was also described in ion channel mutants in D. melanogaster (Vähäsöyrinki et al 2006), suggesting the presence of intrinsic mechanisms that upregulate leak conductance(s) to substitute for a missing ion channel.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to the previous studies involving RNAi of important photoreceptor proteins Saari et al 2017), we found changes in the photoreceptors of Gq and PLC knockdowns, which could not be directly linked to altered gene expression. We, therefore, refer to such changes as non-specific compensations.…”
Section: Changes In Membrane Resistance Capacitance and Absolute Sensupporting
confidence: 88%
See 2 more Smart Citations
“…In vivo intracellular single-electrode recordings were performed as described previously (Saari et al 2017).…”
Section: Intracellular Recordingsmentioning
confidence: 99%